Analysis of rare copy number variation in absence epilepsies. (April 2016) - Addis, Laura; Rosch, Richard E.; Valentin, Antonio; Makoff, Andrew; Robinson, Robert; Everett, Kate V.; Nashef, Lina; Pal, Deb K.
Abstract : Objective: To identify shared genes and pathways between common absence epilepsy (AE) subtypes (childhood absence epilepsy [CAE], juvenile absence epilepsy [JAE], and unclassified absence epilepsy [UAE]) that may indicate common mechanisms for absence seizure generation and potentially a diagnostic continuum. Methods: We used high-density single-nucleotide polymorphism arrays to analyze genome-wide rare copy number variation (CNV) in a cohort of 144 children with AEs (95 CAE, 26 UAE, and 23 JAE). Results: We identified CNVs that are known risk factors for AE in 4 patients, including 3x 15q11.2 deletion. We also expanded the phenotype at 4 regions more commonly identified in other neurodevelopmental disorders: 1p36.33 duplication, 1q21.1 deletion, 22q11.2 duplication, and Xp22.31 deletion and duplication. Fifteen patients (10.5%) were found to carry rare CNVs that disrupt genes associated with neuronal development and function (8 CAE, 2 JAE, and 5 UAE). Four categories of protein are each disrupted by several CNVs: (1) synaptic vesicle membrane or vesicle endocytosis, (2) synaptic cell adhesion, (3) synapse organization and motility via actin, and (4) gap junctions. CNVs within these categories are shared across the AE subtypes. Conclusions: Our results have reinforced the complex and heterogeneous nature of the AEs and their potential for shared genetic mechanisms and have highlighted several pathways that may be important in epileptogenesis of absence seizures.